Physiological and Agronomic Characterisation of Six Cassava Clones (Manihot esculenta Crantz) - Eguiluz, A. (2019)
To evaluate the behaviour of cassava clones (Manihot esculenta Crantz), the physiological quality of the propagation material was assessed, and an agronomic characterisation was conducted; this was essential for the generation of information on the clones’ productive potential. The trial was conducted in the experimental field of the Roots and Tubers programme (PIPS-RT) of the National Agrarian University–La Molina. Following a completely randomised block design with four replications, clones from the PIPS-RT were evaluated. Variables were assessed to determine the clones’ physiological quality in terms of the number of viable stakes, normal seedlings, abnormal seedlings and percentage of stake survival. The agronomic characteristics evaluated were plant height, stem diameter and yield. The Morocha clone had the highest percentage of viable stakes and normal seedlings, i.e. 80.95% and 73.81%, respectively. The highest yield was also produced by the Morocha clones (13 t/ha) followed by the Donoso 2 (7.20 t/ha) and Blanca Cajamarca (6.80 t/ha) varieties.